Being public : musicians and the Market Theatre Cafe, 1976 - 1980 - Ncume, Pakama Sbongile; Matshoba, Pakama Sbongile (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023.